CONCEPTUAL TEASAURUS OF INFORMATION AND DIGITAL COMPETENCE FOR THE FUTURE PEDAGOGICAL WORKER OF PRIMARY EDUCATION - Samborska O. (Kherson State University, 2018)
The article deals with the analysis of modern educational definitions: information and communication competence, ICT competence, computer competence, information and digital competence, digital competency. The content of the informational-digital competence of the pedagogical worker of elementary education is considered and the author's interpretation of this concept is given. In our opinion, the term information and digital competence of a pedagogical worker of primary education should be understood as the teacher's ability to confidently and rationally use information and digital technologies (programs, applications and services) in the process of educational activity among primary school pupils for the purpose of more efficient and effective pedagogical activities and the formation of appropriate skills and abilities in pupils, from the younger age. On the basis of the study of domestic and foreign scientific sources, state legal documents, the author argues that the above concepts go beyond the technological or digital industry. They concern a wide range of educational, culturological, socio-humanitarian and others. aspects. Also, the stages of formation of information and digital competence are described. It contains three components: knowledge, activity, value. Knowledge (cognitive) component involves activating the process of theoretical training. Activity-oriented (practical) component involves gaining practical skills in the field of using information and digital technologies. The value component implies the acquisition of the benefits of using information and communication technologies, as well as understanding the decisive role of ICT in the modern education system. A number of skills that are formed at each stage are defined.